2003
DOI: 10.1046/j.1537-2995.2003.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of adverse citrate reactions during autologous large‐volume PBPC apheresis by continuous infusion of calcium‐gluconate

Abstract: These results indicate that continuous support of calcium-gluconate during LVL is an effective means of reducing the incidence of citrate-related symptoms and improving subjective tolerance toward LVL, without affecting the technical performance or the number of CD34+ cells collected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 28 publications
5
54
1
2
Order By: Relevance
“…In agreement with previous reports [33,48], we did not observe increase in number of adverse events during LVL collection. Buchta et al [49] showed that prophylactic calcium infusion during LVL reduced the incidence of citrate-related symptoms without affecting the technical performance or the number of CD34+ cells collected, as was confirmed by our results. Our study also confirmed marked platelet decrease after processing each TBV with halved platelet count after LVL [3,48].…”
Section: Bojanic 17supporting
confidence: 90%
“…In agreement with previous reports [33,48], we did not observe increase in number of adverse events during LVL collection. Buchta et al [49] showed that prophylactic calcium infusion during LVL reduced the incidence of citrate-related symptoms without affecting the technical performance or the number of CD34+ cells collected, as was confirmed by our results. Our study also confirmed marked platelet decrease after processing each TBV with halved platelet count after LVL [3,48].…”
Section: Bojanic 17supporting
confidence: 90%
“…Apheresis-related key parameters are shown in Table II. During LVL, all patients received a bypass infusion of 8.92 mmol (375.5 mg) calcium diluted in 500 mL of saline to avoid adverse citrate effects, as described previously [15].…”
Section: Mnc Collection With the Cobe Spectra Auto Pbscmentioning
confidence: 99%
“…Hypocalcemia is a toxicity of citrate administration 18,19 and is thought to be more common in pediatric patients receiving citrate than adults. 12,20 Hypocalcemia was screened for in 77% of the donors and measured in 4% (three with ionized Ca 2 þ o0.8 mmol/l (CTC grade 4), one between 0.8 and 0.9 mmol/l (CTC grade 3), and three between 0.9 and 1.0 mmol/l (CTC grade 2)).…”
Section: Complications Of Growth Factor Administration and Apheresismentioning
confidence: 99%